Infeksi Soil Transmitted Healminths (STH) Pada Anak: Analisis Qur’ani Tentang Kebersihan dan Kesehatan - Adine Ulima Rahmatillah (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Soil-Transmitted Helminth (STH) infections remain a significant public health concern in Indonesia, particularly among children. The high prevalence of these infections is closely associated with poor environmental sanitation, inadequate hygiene practices, and low levels of health literacy. This study aims to analyze Qur’anic perspectives on cleanliness and health and examine their relevance to the prevention of STH infections in children. A literature-based method with a thematic (mawḍū‘ī) tafsir approach was employed to explore Qur’anic verses and Prophetic traditions related to ṭahārah, halal and ṭayyib dietary practices, and disease prevention principles. The findings indicate that the Qur’an normatively emphasizes personal and environmental cleanliness, preventive health behavior, and responsible lifestyle practices as integral components of Islamic ethics. These principles are strongly aligned with the modern concept of Clean and Healthy Living Behavior (PHBS). The integration of Qur’anic health values into child health education is therefore considered effective as a holistic promotive and preventive strategy. Consequently, the application of Islamic health principles has the potential to contribute to reducing the risk of STH infections while simultaneously strengthening value-based public health awareness in Muslim communities